A case of infectious heterotopic ossification in the appendectomy scar, which formed an inflammatory granuloma. Issue 8 (17th August 2022) - Hayashi, Chie; Takahashi, Yusuke; Mori, Kiyoshi; Kawai, Kenji; Miyo, Masaaki; Toshiyama, Reishi; Sakai, Kenji; Hamakawa, Takuya; Doi, Takashi; Takeno, Atsushi; Gotoh, Kunihito; Miyazaki, Michihiko; et al.
Abstract: Inflammatory granulomas often develop in surgical scars due to the presence of foreign bodies, such as sutures. These granulomas are called Schloffer's tumors. Here, we report a case of heterotopic ossification(HO) in an appendectomy scar that formed an inflammatory granuloma following HO infection. A 90-year-old woman was referred to our hospital with a chief complaint of a painful mass in the right lower quadrant of her abdomen. She had a history of acute appendicitis, for which she underwent an appendectomy approximately 70 years previously. Imaging studies demonstrated a tumor containing a linear-shaped agent located in the abdominal wall under the surgical scar where the appendectomy was performed. She was then diagnosed with Schloffer's tumor, for which she underwent surgical resection. However, histopathological examination revealed that the tumor was a fibrous connective tissue mass with a lamellar bone inside.